The effects of nutrients on the growth and quality of medicinal and aromatic plants, affecting athletic abilities - Mohammad Miransari; Shirin Adham; Mahdiar Miransari; Amir Arshia Miransari (Journal of Trace Elements and Minerals)
Background: Although the use of medicinal and aromatic plants (herbs and fruits) has become popular, worldwide, more has yet to be indicated on their applications, due to their significance from economic and health aspects. Medicinal and aromatic plants are used for treating diseases and improving the nutrition and health of people including athletes. Objectives and methods: It is accordingly pertinent to find and use methods, which may improve growth and biochemical properties of medicinal and aromatic plants. The objective was to investigate how macro- and micro-nutrients may effectively enhance the quantity and quality of medicinal and aromatic plants by regulating plant biochemical properties (production of secondary metabolites) and increasing plant growth and quality in different conditions including stress. This may also be of significance for the athletic activities. Results: High number of related research and review articles were consulted, which indicated medicinal and aromatic plants and chemical supplements can be used to promote athletes' health and improve their athletic performance. This investigation also revealed that the production of free radicals during exercise may unfavorably affect athletes' health, however, the use of medicinal and aromatic plants may be a favorite method to diminish such unfavorite effects and enhance athletes' health. The use of soil microbes may also enhance the growth and physiology of medicinal and aromatic plants in different conditions by enhancing plant nutrient uptake and subsequent alleviation of stress. Conclusion: In the present review the most recent research about the effects of nutrients on the growth and physiological properties of medicinal and aromatic plants and their subsequent effects on the athletes' health have been reviewed and analysed. Planning a suitable nutritional strategy for the athletes using chemical supplements and medicinal and aromatic plants can significantly improve their performance. The review can be beneficial for promoting people's health including athletes in the society, which is also of economic significance as it may decrease the expenses spent for medical treatment in the society.